Pengaruh Kompres Jahe Merah Terhadap Tingkat Nyeri Haid Pada Remaja di Mts Tanwiriyyah Cianjur - Rania Zahra Aprianti; Nur Eni Lestari; Eka Rokhmiati Wahyu P (STIKes Ibnu Sina Ajibarang, 2024)
Teenagers who menstruate generally experience pain in the abdominal area. One of the complementary therapies that can be given is a red ginger compress. The aim of this research was to determine the effect of red ginger compresses on the level of menstrual pain in adolescents. This research uses a quantitative research method, namely a quasi- experimental approach with purposive sample data analysis using marginal homogeneity with a sample of 15 respondents. Results: There is an effect of red ginger compress on the level of menstrual pain in adolescents.